Size-frequency distribution of earthquakes in hierarchically organized load-transfer models - J. B. Gómez; A. F. Pacheco (Nonlinear Processes in Geophysics, 1997)
Large hierarchically organized sets of elements (simulating asperities in a fault) are loaded to the point of complete failure. The fracture thresholds of individual elements are stochastically distributed, and the hierarchical structure for load-transfer is of the fractal-tree type. During the breakdown process there occur bursts (earthquakes) of several elements breaking simultaneously at a given load. Using Monte Carlo simulations we compute the frequency of bursts versus their size. This shows a gross power-law behaviour superimposed by a wavy pattern closely related to the coordination number of the fractal tree used for the load-transfer structure.